Safari WebKit development for iPhone OS 3.0 - Wagner, Richard 1966- (Wiley, 2010)
With the unparalleled success of iPhone and iPod touch, iPhone OS 3.0 has emerged as a compelling platform for which vast numbers of web developers are designing and building web-based mobile applications. This book explores the Safari and WebKit development platform that is built into iPhone OS 3.0 and takes you through the process of creating an iPhone web application from the ground up. You'll learn how to use existing open source frameworks to speed up your development time, imitate qualities of built-in Apple apps, cache data locally and even run in offline mode, and more. Whether you're eager to build new web applications for iPhone OS 3.0 or optimize existing web sites for this platform, you have everything you need to do so within these pages.--Back cover.
"Wrox programmer to programmer"--Cover. - Includes index. - Print version record
Keywords: iPhone (Smartphone) -- Programming; Mobile computing; Application software -- Development; iPhone (Téléphone intelligent); Programmation; Informatique mobile; Logiciels d'application; Développement; REFERENCE; General; Application software; Development